Fat-augmented latissimus dorsi myocutaneous flap for total breast reconstruction: A report of 54 consecutive Asian cases. Issue 6 (June 2021) - Taminato, Mifue; Tomita, Koichi; Nomori, Michiko; Maeda, Daisuke; Seike, Shien; Tashima, Hiroki; Yano, Kenji; Kubo, Tateki
Summary: Immediate fat grafting to the latissimus dorsi myocutaneous (LD) flaps is a breakthrough that addresses the issue of insufficient volume of LD. However, the use of this procedure in Asian patients has not yet been reported. Retrospective chart reviews were conducted on 54 Japanese cases of total breast reconstruction using fat-augmented LD flaps at our hospital from September 2017 to June 2019. There were 24 immediate reconstruction cases, 18 immediate two-stage reconstruction cases, nine delayed reconstruction cases, and three delayed two-stage reconstruction cases. Median age was 46 years (range, 29–69 years), and median body mass index was 21.5 (17–33.8). Median mastectomy specimen and flap weight was 225 g (123–993) and 225 g (130–796), respectively. The median volume of fat graft was 114 ml (46–305) for the LD flap and 58 ml (15–200) for the pectoralis major muscle. Of the 53 completed reconstruction cases, 38 (71.7%) achieved sufficient volume with the initial operation and six (11.3%) required additional fat grafting. The proportion of cases in the immediate reconstruction group, which achieved sufficient volume in the initial operation was significantly higher than those of the other three reconstruction groups ( p = 0.007). Total breast reconstruction with fat-augmented LD flaps is a viable procedure for thin patients who have insufficient abdominal tissue, for those who wish to avoid abdominal scars, and for those in whom abdominal flaps have already been used. The procedure allows for large volume transplantation even with small skin paddles, which allows for smaller skin paddles to be designed without the need for extensive subcutaneous dissection.